Literasi Islam Santun dan Toleran: Pendampingan terhadap Kelompok Muslim Milenial untuk Mencegah Arus Radikalisme-Ekstrim di Soloraya - Mokhamad Zainal Anwar; Nur Kafid; Khasan Ubaidillah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Solo is an area with a high level of diversity, in terms of ethnicity, culture and religion. Besides of being known as the center of Javanese culture, Solo is also noted to have a high level of intensity of radical-extremism movements. Various efforts to prevent the increasing strong currents of extreme-radicalism are also important to be done. Islamic literacy for courteous and tolerant movement is one of form to prevent extreme-radicalism movement. This program is carried out with a model of direct assistance to millennial Muslim groups in the context of campaigning for a courteous and tolerant Islam. By involving millennial Muslim groups from the high school to university level, this program seeks to prevent the spread of radical-extreme movements among young people in Soloraya area. The mentoring process is carried out through several stages, starting from deepening various authoritative sources on courteous and tolerant Islamic values ​​through the santri camp to public campaigning in the Solo car free day arena. The results show that millennial Muslim groups in Soloraya have succeeded in campaigning for the values ​​of courteousness and tolerance in Islam in a variety of creative ways so as to demonstrate the importance of a tolerant voice in the midst of the image of Solo which is perceived as the basis for the extreme-radical groups movement.